Problematika Pendidikan Berbasis Teknologi Digital di Era Post-Truth dan Urgensi Pendidikan Moral - Babys, Pedro; Pramana, Oktovianus Yudha (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article aims to analyze the problems of digital technology–based education in the post-truth era from the perspective of moral philosophy and to highlight the urgency of moral education in fostering students’ ethical awareness. The study employs a qualitative method using a literature review and descriptive-analytical approach to relevant works on educational digitalization, moral philosophy, and the post-truth phenomenon. The findings indicate that while digitalization seeks to enhance educational access, it has also generated moral challenges such as the decline of critical thinking, technological dependency, and the rise of plagiarism caused by instant mentality and post-truth cognitive bias. These conditions give rise to “digital unconsciousness,” a weakening of ethical awareness in technology use. The paper argues that character education alone is insufficient because it promotes moral habituation without critical reflection. Moral philosophy provides a normative and critical framework—through inductive, deductive, and reflective methods—to ethically evaluate human actions. In conclusion, moral education grounded in moral philosophy is essential to cultivate rational awareness, ethical responsibility.